Follicle-stimulating hormone is expressed in ovarian follicles of chickens and promotes ovarian granulosa cell proliferation - Yu-lin BI; Shu-yan YANG; Hai-yan WANG; Guo-bin CHANG; Guo-hong CHEN (Journal of Integrative Agriculture)
Follicle-stimulating hormone (FSH), an important hypothalamic-pituitary-gonadal axis (HPG) hormone, is secreted by the pituitary gland. This study confirms that FSH is expressed in chicken follicles at different stages, and positive FSHβ mRNA signals were stronger (P<0.05) in granulosa cells than in oocytes. The 369 bp coding sequence of FSHβ in ovaries is 100% identical to that in the pituitary gland. The experiment in vitro revealed that the ovary possessed FSH secretory capacity. Further, FSHβ mRNA was significantly upregulated (P<0.05) in follicles and significantly higher (P<0.05) than that in the pituitary gland by approximately 2–23 times with the development. The number of granulosa cells decreased significantly (P<0.05) in the cells with siRNA treatment, confirming that the ovarian FSH could promote granulosa cell proliferation. This view was supported by cell cycle analysis and CCND2 and CCNE2 expression. Further research indicated that no difference (P>0.05) was observed between the number of granulosa cells treated with FSHβ siRNA and in exogenous FSH. However, the number of granulosa cells without FSHβ siRNA transfection was significantly higher (P<0.05) for exogenous FSH. This finding suggests that the proliferative effect of exogenous FSH on ovarian granulosa cells depend on endogenous FSH. This study demonstrated that the FSH gene was expressed in chicken follicles and promoted ovarian granulosa cell proliferation, which enriched the theory on HPG axis.